Settlement of Wage Payment of Cafe Employees Bankruptcy Imam Syafi'i Perspective (Case Study of Child Cafe, Medan Area) - Indah Permata Sari; Rahmad Efendi (Warmadewa Press, 2024)
The purpose of this study is to examine, from Imam Syafi'i's point of view, the procedure for resolving employee wage payments in the event of business bankruptcy. A case study was used. conducted at Child Cafe Medan Area, which experienced bankruptcy. The research method includes data collection through interviews with relevant parties and document studies related to the process of paying employee wages when the company is bankrupt. The research results are expected to provide a comprehensive overview of handling employee wages in bankruptcy situations, especially considering the perspective of Islamic law. The analysis will cover aspects such as employee rights in wage payment, the obligations of bankrupt companies, and the possibility of fair and sustainable settlements for both parties. From the perspective of Imam Syafi'i, the settlement of employee wage payments in situations of company bankruptcy should be conducted with attention to the principles of justice and humanity. Companies are obliged to make every effort to fulfill their obligations to employees, even in conditions of bankruptcy. Conversely, employees are also expected to understand the company's situation and be willing to accept fair and realistic settlements.